(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The study is devoted to the issue of introducing a single currency for the EAEU member countries. Despite the current difficult geopolitical situation, the author concludes that the events of 2022 have brought the EAEU significantly closer to the implementation of the idea of a single currency, as a significant increase in foreign trade turnover between Russia and EAEU member countries and the strengthening of the role of national currencies in international settlements. In addition, a comparison of the EAEU single currency and the BRICS single currency, discussions of which began in 2023, is presented.